1986
DOI: 10.1139/b86-313
|View full text |Cite
|
Sign up to set email alerts
|

Increased growth responses induced by a nonpathogenic Rhizoctonia solani

Abstract: A nonpathogenic isolate of Rhizoctonia solani (No. 521, AG-4) induced increased growth in a variety of crops. In field experiments, it was expressed in increases of plant weight, cotton fiber weight, or grain yield. The increases for treated compared with untreated plants were as follows: radish, 13.4–19.8% fresh weight and 28.4–36.0% dry weight; carrot, 30.0–97.6% fresh weight and 55.0–150.5% dry weight; lettuce, 58.4% fresh weight and 61.8% dry weight; cotton, 28.7% fiber weight; wheat, 10.6–25.3% weight per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
2

Year Published

1989
1989
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 13 publications
0
24
0
2
Order By: Relevance
“…3). This has also been reported for isolates that are intrinsically nonpathogenic (Sneh et al, 1986). The plant growth promoting activity of R. solani isolates may be due to nutrient release, production of plant hormones or both, and R. solani has been reported to produce substances with gibberellin-like activity (Aubé & Sackston, 1965).…”
mentioning
confidence: 57%
See 1 more Smart Citation
“…3). This has also been reported for isolates that are intrinsically nonpathogenic (Sneh et al, 1986). The plant growth promoting activity of R. solani isolates may be due to nutrient release, production of plant hormones or both, and R. solani has been reported to produce substances with gibberellin-like activity (Aubé & Sackston, 1965).…”
mentioning
confidence: 57%
“…Nevertheless, they can be arranged in groups based on anastomosis, the process of hyphal fusion between isolates (Richter & Schneider, 1953;Parmeter et al, 1969). To date, 12 different anastomosis groups (AGs) are recognized (Sneh et al, 1986;Carling et al, 1994). Of these, AG-1, AG-2, AG-4, AG-6, AG-8 and AG-9 have been subdivided, based on symptoms on rice (AG-1), hyphal fusion frequency (AG-2), zymography (AG-8) or DNA base-sequence homology comparison (AG-4, AG-6 and AG-9).…”
Section: Introductionmentioning
confidence: 99%
“…Sneh et al (1986) reported these effects on the growth of radish, carrot, lettuce, cotton and wheat seedlings and Harris et al (1993Harris et al ( , 1994 found similar phenomena in pepper and some ornamental species. Finally, Sneh et al (1986) and Bandy and Tavantzis (1990) observed in potato seedlings inoculated with hypovirulent isolates of R. solani AG 3, that biomass rates were increased and early tuberization and flowering occurred compared to untreated controls. These effects on potato plants were also reported in Spain by González et al (2000).…”
Section: Pathology and Hypovirulence In The Complexmentioning
confidence: 77%
“…Porém, como método de inoculação, as sementes foram cobertas com substrato infestado com micélio de R. solani AG1-IB -isolado RH 12 (Silveira et al, 2000). O isolado fúngico foi mantido desidratado em flocos de aveia (Sneh et al, 1986). Para produção do inóculo, o fungo foi repicado para meio de batata-dextrose-ágar (BDA) e incubado por três dias a 25ºC no escuro.…”
Section: Solaniunclassified